Park futures: Excavating images of tomorrow's urban green spaces. (September 2020) - Barker, Anna; Crawford, Adam; Booth, Nathan; Churchill, David
British urban parks are a creation of the 19th century and a central feature in the Victorian image of the city. In the UK, parks are at a critical juncture as to their future role, prospects and sustainability. This article contributes to renewed interest in 'social futures' by thinking forward through the past about the trajectory of Victorian public parks. We outline six images of what parks might become, derived from traces in history and extrapolations from current trends. These projections diverge in terms of adaptations to funding and governance, management of competing demands and organisation of use. In contrast to a dominant Victorian park ideal and its relative continuity over time, we are likely to see the intensification of increasingly varied park futures. We draw attention to interaction effects between these differing images of the future. Excavated from the Victorian legacy, the park futures presented have wider potential inferences and resonance, including beyond the UK. By mapping divergent visions for parks, we call for a public debate about how parks might be re-imagined in ways that draw upon their rich heritage and highlight the pivotal role of civil society actors in shaping future pathways between possible, probable and preferable futures.